RELATIONSHIP BETWEEN THE GENERAL PSYCHOLOGY AND FORENSIC PSYCHOLOGY CRITERIA OF PSYCHOLOGICAL INFLUENCE (MARKETING COMMUNICATION CASE STUDY) - V. Gvozdev (Теория и практика судебной экспертизы, 2016)
The paper discusses the issue of criminal psychological influence, and highlights the importance of the problem in the context of forensic practice. Several possible strategies for tackling this problem are proposed, based on the synthesis of categories from general psychology and law. To illustrate the approach, the author analyzes an case of criminal psychological influence.